Molecular Alchemy: Converting Stress into Resilience via Secondary Metabolites and Calcium Signaling in Rice - Muhammad Ikram; Maria Batool; Maaz Ullah; Burhan Khalid; Ali Mahmoud El-Badri; Ibrahim A. A. Mohamed; Lei Zhang; Jie Kuai; Zhenghua Xu; Jie Zhao; Jing Wang; Bo Wang; et al. (Rice)
Abstract Salt stress impairs plant growth by disrupting osmotic regulation, ion homeostasis, and oxidative stress management. Plants respond by activating defense mechanisms, including the biosynthesis of secondary metabolites (SMs) such as alkaloids, flavonoids, terpenoids, and glucosinolates (GSLs). Calcium (Ca2⁺) signaling is central to these responses, acting as an early stress signal. Ca2⁺ influx triggers calcium-dependent protein kinases (CDPKs) and other signaling molecules, which activate stress-responsive genes. SMs are pivotal in mitigating salt stress by promoting osmotic adjustment, maintaining cellular turgor, and modulating ion transporters to reduce Na⁺ uptake and enhance K⁺ retention. This ion homeostasis is closely regulated by Ca2⁺ signaling, which influences transport proteins like Na⁺/K⁺ transporters and vacuolar calcium exchangers (e.g., OsCAX1). The crosstalk between SMs and Ca2⁺ exhibited a critically important role in salt tolerance, as Ca2⁺ influx is an essential trigger for calcium-dependent signaling pathways. Additionally, Ca2⁺ signaling regulates the biosynthesis of SMs through transcription factors like MYB and WRKY. These SMs help detoxify reactive oxygen species (ROS) by regulating antioxidant enzymes such as superoxide dismutase (SOD) and catalase (CAT), aided by MAPK signaling cascades. SMs also interact with abscisic acid (ABA) signaling to regulate stomatal closure and stress-related gene expression, enhancing the plant’s resistance to salt stress. Recent meta-QTL analysis has identified key loci involved in SM biosynthesis and Ca2⁺ signaling pathways under saline conditions, providing promising targets for breeding salt-tolerant crops. This review explores the molecular mechanisms and regulatory networks of SMs and Ca2⁺ signaling in plant salt stress responses, with potential applications in sustainable agriculture. Graphical Abstract